Say hello to Zorro! - Goodrich, Carter (Simon & Schuster Books for Young Readers, 2011)
Mister Bud, the family dog, has a satisfying routine to his life, but when another dog joins the family and disrupts his schedule, Mister Bud must learn to adapt.